Mixed Reality Sandbox Game Development for Improving Disability Children Fine Motor Skill - Lukman Hakim; Muhamad Fuad Al Haris; Eka Mistiko Rini; Dedy Hidayat Kusuma (TEPIAN, 2023)
One of the categories of disabled children is a double disability with two or more barriers, such as blind and deaf (Multiple Disabilities with Visual Impairments / MDVI). MDVI children with vision lower or less than Normal vision (low vision) tends to experience motor problems due to a lack of received external stimuli. From previous research, the three learning areas of MDVI children with low vision improved gradually, but the motor skills that support these activities are not optimal. This is because motor movement exercises are not enough just to be presented in visual form but require natural movement from body movements. Therapeutic use playing with sand is effective in stimulating motor movements in children. But its application to MDVI children with low vision has not been tested. In addition, loop repetitive motor training reduces motivation to practice because the training environment is monotonous. Provides an interactive training environment and supports the stimulus aspect visuals such as lighting, contrast, object size, and visualization distance can increase motivation and exercise compliance. The use of a virtual environment (virtual environments / VE) such as mixed reality (MR) can provide a training environment adaptive and produces deeper sensations in the brain (immersion) for exercise extremity motor movements. However the use of interventions is Unprecedented interactive and dynamic practice environment sand-based games applied to help exercise motor skills in MDVI children with low vision. The development of serious games is proposed using a mixed reality-based sandbox game device (MR-Sandbox) for motion therapy upper limb motor skills for MDVI children with low vision by combining reinforcement of visual stimuli to stimulate the activation of the corticospinal nervous system through combining real and virtual activities (mixed reality) and creative visualization using sand media (virtual topography) in promoting fine motor movements. This study uses a quasi-experimental design research method, pre-test, and post-test. The sampling technique uses purposive sampling of 12 MDVI respondents with low vision (eight men, eight women) in the sand-type educational game intervention group. The Assessment uses sheets Denver II instrument, which is taken from the aspect of acceptable motor measurement. Data analysis is the t-test of 2 dependent samples and the t-test of 2 independent models for bivariate.